(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The involvement of investment process requires proper decision-making agendas by which the investor can have security to their equity. The increasing financial conditions of women for becoming self-independent are one of the reasons for them to invest in mutual funds. The sociability and personality traits have helped in findingbehavioral trends among the women of Tamilnadu. This study has been done based on the empirical study for collection of the data using secondary method.